2018
DOI: 10.1111/vcp.12645
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional statistical quality control using commercially available control materials and two patient‐based quality control procedures for the ADVIA 120 Hematology System

Abstract: Patient-based procedures are suitable for veterinary laboratories. The RPT approach may benefit laboratories with limited budgets and low hematology caseloads. The AoN procedure may benefit laboratories with higher hematology caseloads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…19,20 These findings could explain the initially sta- In one report of duplicate analysis of canine platelet counts using the first-generation ADVIA 120 over 25 days, the overall CV was 12.23%. 35 The CVs calculated in our study were similar, except for Citrate ADP and AGGFix ADP. The higher CV for Citrate ADP platelet counts likely reflects both less precision of platelet counting in citrate compared with EDTA, 28 and possibly rapid changes in platelet aggregation between duplicate runs, as during optimizing studies, very rapid platelet disaggregation was noted (data not shown).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…19,20 These findings could explain the initially sta- In one report of duplicate analysis of canine platelet counts using the first-generation ADVIA 120 over 25 days, the overall CV was 12.23%. 35 The CVs calculated in our study were similar, except for Citrate ADP and AGGFix ADP. The higher CV for Citrate ADP platelet counts likely reflects both less precision of platelet counting in citrate compared with EDTA, 28 and possibly rapid changes in platelet aggregation between duplicate runs, as during optimizing studies, very rapid platelet disaggregation was noted (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…Equivalent data for dogs are not available. In one report of duplicate analysis of canine platelet counts using the first‐generation ADVIA 120 over 25 days, the overall CV was 12.23% 35 . The CVs calculated in our study were similar, except for Citrate ADP and AGGFix ADP.…”
Section: Discussionsupporting
confidence: 72%
“…This differed from prior recommendations to collect 20 data points 9 and prior studies that were able to validate limits determined using 20 data points. [10][11][12] Following the RPT-QC limit generation, the validation process required calculation of limits using 30-40 data points for more than half of measurands/time interval evaluations. We found that by only using 20 results, the data were either not included within the control limits or did not adequately fill the range, but when an additional 10-20 data points were used, then we saw a better distribution across the QC data range.…”
Section: Discussionmentioning
confidence: 99%
“…9 The difference between original and repeated analyses can then be calculated and plotted similarly to other QC procedures. 7 There have been some positive reports in the literature [10][11][12] that indicate a good potential for application in veterinary laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods using patient samples have been described and found to be both practical and successful at evaluating the function of veterinary hematology analyzers. [16][17][18] These strategies each have their own benefits and drawbacks.…”
Section: Opp Ortunitie S For Improving the Future Of Qcmentioning
confidence: 99%